Hubungan Tingkat Pendidikan Ibu Hamil Dan Perilaku Pelayanan Bidan Terhadap Katuhanibu Hamil Dalam Mengkonsumsi Tablet Fe Di Puskesmas Gatakkabupaten Sukoharjo - Sari, Arum, Dwi Sarbini, S.ST., M.Kes, Irma Budi Hapsari, S.SiT (2014)
Background:Anemia in pregnancy is caused by iron deficiency and acute hemorrhage. Iron deficiency anemia in pregnant women caused by attitude of pregnant womens in consumed iron tablet are not good or the way how to consume iron tablet is wrong causing a lack of absorption of iron in the body. Low levels of education correlated with the level of understanding of the iron tablet and awareness of the consumption of iron tablets for pregnant women. Compliance can be improved if the midwifes, doctor, and nutritionist is able to provide nutrition counseling expecially about benefit of iron tablet and pregnant women's healthy. Purpose: To know correlation between education of pregnant women and behavior of midwifes in antenatal care with compliance of pregnant womens in consumed tablet of fe at Gatak's Public Healt Center Of Sukoharjo Regency. Method of the Research: The research implemented a survey-observationalwith cross-sectional approach. Subject of the research is 67 individuals selected by using simple random sampling. Data of education of pregnant women,behavior of midwifes and compliance was taken by used a questionnaire. Data is analyzed by using correlation test of Chi-square. Result: most of respondents hadbasic education of 59,7%, most of behavior midwifes was being good of 82,1%, and most of respondents was not disobedient of in consumed iron tablet of 58,2%. Conclusion: there had not correlation between education l care with compliance of pregnant womens and there had correlation between behavior of midwifes in antenatal care with compliance of pregnant womens in consumed tablet of Fe at Gatak's public healt center of Sukoharjo regency